2023
DOI: 10.1103/physrevc.108.054301
|View full text |Cite
|
Sign up to set email alerts
|

High-precision measurements of low-lying isomeric states in In120124 with the JYFLTRAP double Penning trap

D. A. Nesterenko,
J. Ruotsalainen,
M. Stryjczyk
et al.

Abstract: High-precision measurements of low-lying isomeric states in 120-124In with the JYFLTRAP double Penning trap

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 81 publications
2
6
0
Order By: Relevance
“…In this work, the mass-excess value of the 118 In first isomeric state was determined directly for the first time and it is 107 (50) keV lower than the NUBASE20 extrapolation [39] while that of the second isomeric state is 108 (50) keV lower. It should be noted that the firstisomer mass excess, = −87236.8 (16) keV, is in agreement with the literature value for the ground-state mass excess, lit. = −87228 (8) keV [4].…”
Section: B 117-119 Insupporting
confidence: 91%
See 4 more Smart Citations
“…In this work, the mass-excess value of the 118 In first isomeric state was determined directly for the first time and it is 107 (50) keV lower than the NUBASE20 extrapolation [39] while that of the second isomeric state is 108 (50) keV lower. It should be noted that the firstisomer mass excess, = −87236.8 (16) keV, is in agreement with the literature value for the ground-state mass excess, lit. = −87228 (8) keV [4].…”
Section: B 117-119 Insupporting
confidence: 91%
“…3. A comparison of (a) two-neutron separation energies S 2n and (b) two-neutron shell-gap energies δ 2n for the In isotopic chain between AME20 [4], the work by Nesterenko et al [16], where mass values of [120][121][122][123][124] In are reported, and the combined results from JYFLTRAP (this work and Nesterenko et al [16]). The close-up of the S 2n curve around N = 70 is plotted in the inset.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations